Study of the physical and mechanical properties of hosiery products made from bamboo yarn - Jo'rabayev, Nozimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this scientific study, the physical and mechanical properties of hosiery products produced by mixing cotton, polyester, viscose and spandex yarns in different proportions with bamboo yarn were studied. In this study, by improving the yarn feeding system of a single-needle KJ606F 156-needle hosiery knitting machine, it was achieved to obtain a closed glad weave. During the study, 4 types of hosiery products were developed and recommendations were given to manufacturing enterprises.